Business Tradition: Qualitative Assessment on The Economic Commodification of Larung Sesaji Ritual for Local MSMEs - Paramita Kartika Sari; Mariatus Sholikah (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the economic commodification of the Larung Sesaji ritual and its contribution to the development of local micro, small, and medium enterprises (MSMEs) at Kenjeran Beach, Surabaya. It also explores how local communities balance cultural preservation with economic interests in tourism development. Research Method: This study employed a qualitative business ethnography approach. Data were collected through observations, interviews, documentation, and field notes involving key stakeholders and analyzed using an interactive data analysis model. Results and Discussion: The findings indicate that the Larung Sesaji ritual serves not only as a sacred cultural tradition but also as an economic catalyst that stimulates local entrepreneurship through culinary businesses, handicrafts, souvenir production, and tourism services. Cultural commodification does not necessarily reduce ritual authenticity when local communities maintain control over cultural representation and decision-making. Community-Based Tourism enhances participation, strengthens local economic resilience, and supports sustainable destination management. Implications: The findings provide practical guidance for policymakers and tourism stakeholders in designing inclusive and culturally sustainable tourism strategies while supporting MSME development and community welfare. Originality: This study integrates business ethnography, cultural commodification, and Community-Based Tourism to explain cultural heritage as a sustainable economic resource.